Molecular Hydrogen: A Promising Adjunctive Strategy for the Treatment of the COVID-19 - Li, Yingning; Wang, Zhen; Lian, Naqi; Wang, Yuzun; Zheng, Weiqiang; Xie, Keliang (Frontiers in Medicine, 2021)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease induced by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which has no specific and effective treatment. The pathophysiological process of COVID-19 is an excessive inflammatory response after an organism infects with a virus. Inflammatory storms play an important role in the development of COVID-19. A large number of studies have confirmed that hydrogen has a therapeutic effect on many diseases via inhibiting the excessive inflammatory cells and factors. Recently, a study led by Academician Zhong Nanshan in China on the treatment of COVID-19 patients by inhalation of a mixed gas composed of hydrogen and oxygen has attracted widespread international attention, and hydrogen therapy has also been included in a new treatment plan for COVID-19 in China. Accordingly, this article mainly describes the occurrence mechanism of COVID-19, summarizes the therapeutic effects and underlying mechanisms of hydrogen on the critical disease, and analyzes the feasibility and potential therapeutic targets of hydrogen for COVID-19 treatment.